2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591550
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the outcome in cardiac arrest patients undergoing hypothermia using EEG wavelet entropy

Abstract: Cardiac arrest (CA) is the leading cause of death in the United States. Induction of hypothermia has been found to improve the functional recovery of CA patients after resuscitation. However, there is no clear guideline for the clinicians yet to determine the prognosis of the CA when patients are treated with hypothermia. The present work aimed at the development of a prognostic marker for the CA patients undergoing hypothermia. A quantitative measure of the complexity of Electroencephalogram (EEG) signals, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We found that information theoretic measures of EEG complexity and regularity were predictive of good functional outcomes while features measuring epileptiform discharges were associated with poor outcomes. (5,17,19,22,26,41,42) Two EEG complexity features (Cepstrum and Tsallis entropy) and EEG regularity contributed to predictions in the first 24 hours of monitoring. These findings substantiate prior reports that specific EEG signatures observed during the first 24 hours after cardiac arrest have strong predictive value despite hypothermia and sedative use.…”
Section: Discussionmentioning
confidence: 99%
“…We found that information theoretic measures of EEG complexity and regularity were predictive of good functional outcomes while features measuring epileptiform discharges were associated with poor outcomes. (5,17,19,22,26,41,42) Two EEG complexity features (Cepstrum and Tsallis entropy) and EEG regularity contributed to predictions in the first 24 hours of monitoring. These findings substantiate prior reports that specific EEG signatures observed during the first 24 hours after cardiac arrest have strong predictive value despite hypothermia and sedative use.…”
Section: Discussionmentioning
confidence: 99%
“…According to the complexity theories, somewhat higher complexity is associated with relatively improved health conditions and greater chances of survival (Costa et al, 2002a , 2005 ), while a reduction in or loss of complexity is often associated with imbalance or disturbed physiological conditions, usually implying disease or aging (Goldberger et al, 2002 ). In many studies, complexity-based metrics of the dynamics of a physiological system have demonstrated better prognostic power (Mejaddam et al, 2013 ; Lin et al, 2014 ; Vandendriessche et al, 2014 ; Moshirvaziri et al, 2016 ; Chiu et al, 2017 ; Ma et al, 2017 ). The complexity theories also suggest that different levels of complexity can indicate whether a system is under stress or relatively relaxed (Costa et al, 2002a , 2005 ; Goldberger et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%